Ketogenic Keys to Body Composition: Nutritional Insights and Comparative Dietary Effects - Kelnia Mellenia; Santoso, Alexander Halim (HM Publisher, 2024)
Background: The ketogenic diet, characterized by high fat, low carbohydrate intake, has garnered significant interest for its impact on body composition. Despite its popularity, the mechanisms and long-term effects of the diet remain subjects of ongoing research and debate within the medical and nutritional science communities. Methods: This review systematically examines peer-reviewed clinical trials, observational studies, and comparative analyses conducted from 2004 to 2024. Studies were selected based on their relevance to the ketogenic diet's effects on body composition, adherence to rigorous methodological standards, and the provision of clear outcome measures related to fat mass, lean muscle mass, and overall weight changes. Results: The review synthesizes findings to elucidate the diet's mechanisms, effects, and comparative performance against other dietary interventions. The ketogenic diet induces metabolic adaptations conducive to fat loss while potentially preserving lean muscle mass, mediated through ketosis and associated hormonal shifts. Comparative analyses suggest that the ketogenic diet may offer distinct advantages in fat reduction compared to low-fat and Mediterranean diets, attributed to its profound effects on metabolic pathways and satiety regulation. However, individual responses vary significantly, influenced by factors such as exercise, diet duration, macronutrient composition, and genetic predispositions. Conclusion: The ketogenic diet emerges as a potent intervention for altering body composition, particularly effective in reducing fat mass. Its unique metabolic and hormonal effects distinguish it from other dietary approaches. Nevertheless, considerations regarding the diet's long-term sustainability, potential risks, and individual variability underscore the need for personalized dietary planning and further research.